The psychic costs of migration: Evidence from Irish return migrants - Alan Barrett; Irene Mosca (Institute for the Study of Labor (IZA), 2012)
Within the economics literature, the psychic costs of migration have been incorporated into theoretical models since Sjaastad (1962). However, the existence of such costs has rarely been investigated in empirical papers. In this paper, we look at the psychic costs of migration using alcohol problems as an indicator. Rather than comparing immigrants and natives, we look at the native-born in a single country and compare those who have lived away for a period of their lives and those who have not. We use data from the first wave of the Irish Longitudinal Study on Ageing (TILDA) which is a large, nationally representative sample of older Irish adults. We find that men who lived away are more likely to have suffered from alcohol problems than men who stayed. For women, we again see a higher incidence of alcohol problems for short-term migrants. However, long-term female migrants are less likely to have suffered from alcohol problems.
urn:nbn:de:101:1-2012042310941
Keywords: F22; J61; I10; 330; migrants; psychic costs of migration; alcoholism; Migranten; Rückwanderung; Psychische Störung; Alkoholkonsum; Irland